ECONOMIC AND SOCIAL ISSUES IN SUSTAINABILITY - Ahmad Jusoh, editor 380585; Ungku Norulkamar Ungku Ahmad, 1968-, editor 509501; Adaviah Mas'od, 1988-, contributor 644146; Ahmad Jusoh, contributor 380585; Aslan Amat Senin, contributor 559432; Sasitharan, D. contributor 652136; Goh, Kar Hei, contributor 652137; Halim Mad Lazim, contributor 652139; Hakimah Muhammad Zin, contributor 646010; Herman Shah Anuar, contributor 652141; Huam, Hon Tat, contributor 359156; Hang, See Pheng, 1982-, contributor 577028; et al. (Johor Bahru, Johor : PENERBIT UTM PRESS, 2023)
Includes bibliographical references and index.